Atomic and electronic structures of stable linear carbon chains on Ag-nanoparticles. (March 2018) - Boukhvalov, D.W.; Zhidkov, I.S.; Kurmaev, E.Z.; Fazio, E.; Cholakh, S.O.; D'Urso, L.
Abstract: In this work, we report X-ray photoelectron (XPS) and valence band (VB) spectroscopy measurements of surfactant-free silver nanoparticles and silver/linear carbon chains (Ag@LCC) structures prepared by pulse laser ablation (PLA) in water. Our measurements demonstrate significant oxidation only on the surfaces of the silver nanoparticles with many covalent carbon-silver bonds but only negligible traces of carbon-oxygen bonds. Theoretical modeling also provides evidence of the formation of robust carbon-silver bonds between linear carbon chains and pure and partially oxidized silver surfaces. A comparison of theoretical and experimental electronic structures also provides evidence of the presence of non-oxidized linear carbon chains on silver surfaces. To evaluate the chemical stability, we investigated the energetics of the physical adsorption of oxidative species (water and oxygen) and found that this adsorption is much preferrable on oxidized or pristine silver surfaces than the adsorption of linear carbon chains, which makes the initial step in the oxidation of LCC energetically unfavorable. Graphical abstract: Image